Teknologi Penyiapan Pupuk Organik Babadotan (Ageratum conyzoides) terhadap Kimia Tanah dan Tanaman Bawang Dayak (Eleutherine palmifolia) pada Tanah Ultisol - Najerah, Norhamidah; Ifansyah, Hairil; Yusran, Fadly H. (Universitas Lambung Mangkurat, 2023)
Ultisol land is the largest part of dry land in Indonesia, which is about 25% of the total land area of Indonesia or 45,794,000 hektare. Ultisol soil is classified as low, this is indicated by very low organic matter content, acid soil reaction, low base saturation, high Al content, and low productivity. Increasing the productivity of Ultisol soil can be done through soil improvement (amelioration), fertilization and organic matter. Babadotan (Ageratum conyzoides) can be used as an alternative source/material for organic fertilizer, especially if the availability of other sources of organic fertilizer is very limited. Babadotan gave the largest contribution of N, P and K nutrients compared to other weeds, namely 6.3 ; 0.5 ; 4.7 kg ha-1. Study aims for determine the effect of various technologies for preparing organic fertilizer from babadotan plants on the growth of Dayak onion bulbs. The research was conducted at the Greenhouse, Department of Agroecotechnology, Faculty of Agriculture, from March 2018 to July 2019. The experimental design was a one-factor RAL, namely organic fertilizer with five treatments and four replications, so there were 20 experimental units. Observation parameters consisted of soil reaction, CEC, P-Available, Al-dd, and plant yield observations. The application of dry babadotan organic fertilizer in blender was able to increase the level of available P in the soil with the highest value of 198.15 ppm and the application of fresh babadotan organic fertilizer tended to decrease the level of Al-dd in the soil with a value of 0.27 me/100g.